Estimating Time of Driver Arrival with Gradient Boosting Algorithms and Deep Neural Networks - Sergoyan, Henrik T. (Изд-во НАН РА)
Customer experience and resource management determine the degree to which transportation service providers can compete in today's heavily saturated markets. The paper investigates and suggests a new methodology to optimize calculations for Estimated Time of Arrival (from now on ETA, meaning the time it will take for the driver to reach the designated location) based on the data provided by GG collected from rides made in 2018. Հաճախորդների սպասարկումը և ռեսուրսների կառավարումը որոշում են տրանսպորտային ծառայություններ մատուցող ընկերությունների մրցակցելու կարողության աստիճանը այսօրվա մեծ և հագեցած շուկաներում: Այս աշխատանքն ուսումնասիրում և առաջարկում է նոր մեթոդաբանություն վարորդի ժամանման տևողությունը հաշվարկելու համար` հիմնվելով GG-ի 2018 թվականի ուղևորություններից հավաքված տվյալների վրա: Обслуживание клиентов и управление ресурсами определяют степень, в которой поставщики транспортных услуг могут конкурировать на сегодняшних сильно насыщенных рынках. В этой работе исследуется и предлагается новая методология оптимизации для расчетов предполагаемого времени прибытия водителя на основе прошлогодних данных, предоставленных GG, собранных из поездок водителей компании.
Keywords: Mathematical cybernetics; Computer science